Monographic: On the Fantastic and The Urban - Jose Duarte (Universitat Autònoma de Barcelona, 2017)
Editorial for the monographic section on "ON THE FANTASTIC AND THE URBAN" coordinated by José Duarte and Ana Daniela Coelho.